INVESTIGATION OF THE MODIFICATION INFLUENCE ON THE STRUCTURE, PHASE COMPOSITION AND PROPERTIES OF STEEL 5XHM IN CAST STAT - F. I. Rudnitskij; V. A. Stasiulevich; N. S. Traimak (Литьë и металлургия)
The influence of several modifying elements on the main technological, physical-chemical and service properties of cast die steel 5XHM is investigated in the work. The most perspective modifiers for using in technological process of the cast instrument production are determined.